Influence of different surface treatments on bond strength of a self-adhesive resin cement to CAD-CAM materials = Influencia de los diferentes tratamientos superficiales en la unión del cemento resinoso autoadhesivo a los materiales CAD-CAM - Kaptan, Alper
To evaluate the shear bond strength (SBS) of self-adhesive resin cement when used with two different computer-aided design (CAD)-computer-aided manufacturing (CAM) materials after various surface treatments. Nanoceramic resin Lava Ultimate (LU) and feldspathic ceramic Vita Mark II (VM) CAD-CAM block samples were prepared with 1.5-mm thickness, and a total of 90 samples were obtained (N=90), with five samples of each block. The samples were divided into the following five groups according to the surface treatments (n=9): group 1, untreated (control); group 2,5% hydrofluoric acid etching; group 3, Er: YAG laser irradiation; group 4, tribochemical silica coating (Cojet); and group 5, air-abrasion with Al2O3. After silane application, resin cement was applied on a transparent matrix (diameter, 3mm; height, 2mm) on the blocks. SBS was determined using a universal testing device at a crosshead speed of 1mm/min. Two-way analysis of variance (ANOVA) and Tukey's post hoc tests were used to analyze the SBS values. LU showed the highest SBS value in group 4. The average SBS values in groups 3 and were found to be lower than that in the control group (p<0.05). When VM was examined, while all surface treatments increased the SBS values significantly, the highest SBS value was observed in group 4 (p<0.05). This study revealed that all surface treatments used negatively affected the bond strength values of self-adhesive resin cement to LU, except for Cojet application. The SBS values of resin cement with VM increased in all surface treatment application groups.